Evaluasi Kelayakan Investasi Perumahan Permata Residence Pada PT. Perdana Mulya Ramadhani Developer Dan Real Estate - Adisti Restu Putri (Kredibel: Jurnal Ilmiah Manajemen, 2025)
The thesis is entitled Evaluation of Investment Feasibility of Permata Residence at PT. Perdana Mulya Ramadhani Developer and Real Estate. The type of research used is descriptive research with case study method. Where in this study data collection by looking at a case faced by PT. Perdana Mulya Ramadhani in carrying out an investment in the construction of the Permata Residence housing. The analytical tools used are Net Present Value (NPV) and Payback Period (PP). The results of analysis using the Linear Trend, show that results increase every year in terms of both demand and supply. If seen from the results of calculations using the Net Present Value (NPV) the results are Rp. 18.699.498.976,- which is more than 0, the project is said to be feasible. If we look at the calculation results using the Payback Period (PP), it’s found that the company’s capital will be returned within a period of 3 years 5 months, so this project is said to be feasible because the time required to return the capital is shorter than the time that has been determined for 5 years.